Neuroscience Fifty years in learning and behavior: a neuroscience analytical listening review - Elisabetta Baldi (Electronica, 2017)
This bibliographic material is patrimony of our Laboratory of the Behavior Physiology. This research unit originated in 1972 by will of Aldo Giachetti (until 1990) and with the beginning of the activity of Corrado Bucherelli. In the early 1980s, with Carlo Ambrogi Lorenzini (until 2004), the cataloging became more capillary and systematic, to continue to this day. All the researchers who worked in our laboratory contributed to this collection (Giovanna Tassoni 1986-2000, Benedetto Sacchetti 1996-2002 and Elisabetta Baldi from 1991). The study of learning, memory and behavior requires to follow a broad spectrum of neuroscience topics, ranging from neuronal biochemistry to neuropsychology. The Authors' idea of publishing this collection comes from believing that a such website, though not exhaustive, might be a useful and targeted tool for the selection of bibliographic material in the field of behavioral neuroscience. The bibliographic references present at the publication (29500), accompanied by a brief comment highlighting the contents, are organized in relation to the topics (represented by the 99 themes) constituting the publication itself. The intersection of several references will point out the topics that represent them simultaneously. Concerning neurotransmitters and neuromodulators, references to agonists, antagonists or molecules interfering with the activity of these synapses have been inserted in the pages of the implicated neurotransmitter (e.g. acetylcholine). The pages including topics that could have been dealt with separately (e.g. active and passive avoidance) are introduced by a short explanatory note. The comment of each publication highlights the animal species used. Each comment is intended to indicate the content rather than the experimental results of paper. This choice comes from wanting to provide the reader with a more objective and less speculative comment.